1989
DOI: 10.1111/j.1439-0523.1989.tb00385.x
|View full text |Cite
|
Sign up to set email alerts
|

Observed and Predicted Genetic Gains from Single and Multi‐Trait Selections Using Three Mating Designs in Pearl Millet*

Abstract: The objectives of the study were to estimate the genetie eomponents of varianee, prediet the response to selection and to evaluate observed response to selection using two populations namely, PSB 7 and PSB 3, of pearl millet (Pennisetum americanum [L.] Leeks). The observed response was studied using four methods of seleetion based on single and multitrait eriteria in three types of families, namely SI, half-sib (HS) and full-sib (FS) families. One hundred SI, HS and I'S families eaeh were developed in PSB 7 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(2 reference statements)
1
2
0
Order By: Relevance
“…This finding is in agreement with the findings of Basu (1981) and Abu-Gasim and Kambal (1985) and Bello, et al (2007) for several quantitative for characters in sorghum genotypes. Zaveri et al (1989) also reported similar results in pearl millet. Lukhele (1981) and Bello et al (2007) observed that high error or environmental variance estimate for some characters similar to what was obtained in this study could be attributable to sample size.…”
Section: Resultssupporting
confidence: 68%
“…This finding is in agreement with the findings of Basu (1981) and Abu-Gasim and Kambal (1985) and Bello, et al (2007) for several quantitative for characters in sorghum genotypes. Zaveri et al (1989) also reported similar results in pearl millet. Lukhele (1981) and Bello et al (2007) observed that high error or environmental variance estimate for some characters similar to what was obtained in this study could be attributable to sample size.…”
Section: Resultssupporting
confidence: 68%
“…Exploiting a diverse range of germplasm, mostly from the African sources, several composites were developed and improved by recurrent selection, resulting in the development and dissemination of a large number and diverse range of breeding materials. In population improvement programme, various recurrent selection methods (mass selection, gridded-mass selection, recurrent restricted phenotypic selection, S 1 and S 2 progeny selection, half-sib selection and full-sib selection) with varying successes in the genetic improvement of several trait-based composites have been used [34,36,88,101,140,160]. A large number of trait-based composites (e.g.…”
Section: Population Improvement and Opv Developmentmentioning
confidence: 99%
“…Also, most of characters showed high significance of mean squares due to genotypes and interaction between genotypes and locations, implying that the treatments and genotypes tested across the two seasons were highly diverse. It is worth mentioning in this study that the values of the experimental error or the environmental variance of the studied characteristics are low, while studies confirm that in the case of high values of the experimental error, the sample size is not appropriate due to the number of treatments, season locations and it is an indication of lack of credibility in the results (Zaveri et al, 1989 andBello et al, 2007), and this is not found in this study.…”
Section: Discussionmentioning
confidence: 47%